Sweets consumption of preschool children - extent, context, and consumption patterns - Schneider, Sven; Jerusalem, Moran; Mente, Johannes; Bock, Freia de (Clinical oral investigations, 2013)
Objectives: Sweets consumption is one of the risk factors of caries, especially among children. The aim of our study was to explore the extent and context of preschoolers’ sweets consumption and to identify high-risk groups. Materials and methods: The baseline cross-sectional data used originated from a nutritional intervention study encompassing 879 parental surveys, which were obtained in 52 kindergartens in Baden-Württemberg—the third largest federal state in Germany—between September and March 2009. Our outcome variable “sweets consumption” was operationalized using food-frequency items and analyzed by testing the influence of sociodemographic, educational, cultural, and family context covariates.Results: Most preschoolers consumed sweets every day—on average 9.7 ± 6.2 times per week. Most popular were cookies, gummy bears, and chocolate. Sweets consumption did not correlate significantly with sociodemographic factors like age and sex but rather was associated with cultural and contextual factors such as immigrant background, parental education, specific nutritional knowledge levels, and access arrangements in the home.Conclusions: The consumption patterns identified are a result of high availability and parental influence (factors such as parents’ knowledge levels, interest in, and habits regarding their child’s nutrition).Clinical relevance: Dental practitioners should place more emphasis on gathering information from young patients regarding excessive and frequent consumption of sweets and consequently on trying to educate the children and their parents on oral health risks associated with such consumption. Particular attention is to be paid to children of Turkish and Arabic decent, as they have been shown to consume above-average amounts of sweets.
First online: 07 August 2012
Gesehen am 19.06.2018